Comparative Study of Defected Waveguide Structure with Circuit Modelling - Chin, S. J.; Abd. Aziz, M. Z. A. (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2018)
The comparisons of Defected Waveguide Structure (DWS) are made to determine their performances toward waveguide in Ultrawideband (UWB) frequency range. Initially, the copper waveguide is designed to have a basic square structure as DWS. The straight connecting strip is added on in between the square. The straight connecting strip is then folded to reduce the length. All the designs and simulation process are constructed in CST Microwave software. The results of transmission coefficient (S21) and reflection coefficient (S11) are used for performance analysis. An equivalent circuit is designed and simulated in Advanced Design System (ADS) for modelling purpose based on filter concept. Copper waveguide performs as high pass respond with the frequency more than cut off frequency. Basic square DWS operates from 3.5GHz to 8.25GHz. Meanwhile, basic square DWS with straight and meander line connecting strip operate at a higher frequency from 8.11GHz-9.23GHz and 7.68GHz-10.8GHz, respectively. Basic square DWS with meander line connecting strip operates for the wider bandwidth of 3.12GHz with compact size.